The Application of Read-Answer-Discuss-Explain-and Create (Radec) Models to Improve Student Learning Outcomes in Class V Elementary School on Human Respiratory System - Sukmawati, Dian; Sopandi, Wahyu; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This study aims to improve the learning outcomes of students of class V SDN Sukaraja I related to the concept of human respiratory system through the RADEC model. The research subjects consisted of 34 students. The research method used is Classroom Action Research. The instruments used were tests and non-tests. The test instrument was arranged to measure student learning outcomes. Non-test instruments are used to determine the feasibility of learning. The data obtained consisted of qualitative and quantitative data. Qualitative data were analyzed descriptively while quantitative data were analyzed by finding averages and percentages of achievement in each cycle. This research was validated using triangulation techniques. The results showed that RADEC was able to improve student learning outcomes on the topic of the human respiratory system. This is evidenced by the change in the achievement of students' learning outcomes. In the preliminary data, around 40% or as many as 14 students have reached completion. In the first cycle, an increase in completeness reached 65%, or as many as 22 students achieved completeness. In the second cycle there was also an increase in completeness which was around 90% or as many as 31 students had reached completeness